Perilaku Seks Bebas dalam Konteks Budaya Eropa - Adib Al-Mufakhir (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study examines the phenomenon of casual sex within the context of European culture, particularly in Denmark, Italy, and Germany, which are known for their high levels of acceptance and legalization of premarital sex. Adolescence is a transitional phase marked by physical, psychological, and social changes that influence sexual desire. In several European countries, casual sex is not only socially accepted but also constitutionally legalized on the grounds of individual freedom and the protection of human rights. The aim of this study is to understand how the culture, social norms, and policies of European countries shape their views on casual sex and how this phenomenon differs from the generally negative perceptions prevalent in other countries. The research method used was qualitative with a library research approach through analysis of academic literature, mass media, and public policy documents. The results show that casual sex in Denmark is seen as a freedom of individual expression and is supported through open sex education. Italy places casual sex within the framework of a legally regulated prostitution industry, while Germany makes prostitution a legal occupation with social and health protections for its workers. In conclusion, the culture of casual sex in Europe is rooted in respect for individual freedom and legal regulations aimed at mitigating the negative impacts of sexual criminalization. The implications of this research provide new perspectives on the relationship between public policy, individual freedom, and cultural norms in shaping sexual behavior in modern society.